A reduced switch count UPF power conditioner for grid connected variable speed wind energy conversion system employing PM generators: a simulation study. (13th September 2004) - Raju, A.B.; Fernandes, B.G.; Chatterjee, K.
In this paper, modelling and simulation of a grid connected variable speed wind energy conversion system (VSWECS) with reduced switch count power converter is presented. The system consists of a permanent magnet synchronous generator (PMSG), two pulse width modulated B-4 power converters and a maximum power point tracker (MPPT). Mathematical models of each element of the system are developed separately and are then integrated to simulate the whole system for various wind velocities. The complete system is simulated using MATLAB/SIMULINK and simulation results are presented.